PEMBANGUNAN SARANA DAN PRASARANA TRANSPORTASI DESA DI DESA TERISOLIR - Adhi Darmawan (JURNAL ADMINISTRASI DAN KEBIJAKAN PUBLIK, 2018)
Law No.6/2016 concerning Villages has given the village freedom to be able to prepare plans for meeting basic needs, development of village facilities and infrastructure, development of local economic potential, utilization of natural resources, sustainable environment and village governance. Village transportation facilities and infrastructure are needed, especially for isolated villages. The construction of isolated transportation facilities and infrastructure in the village not only requires a small budget, but also faces several challenges that must be resolved.